Comparison on the chemical composition and antioxidant properties of essential Oil from fresh, boiled and freeze-dried the rhizomes of Curcuma zedoaria - Omar, Nur Izzati; Darnis, Deny Susanti; Bakhtiar, M. Taher (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2019)
Introduction: Curcuma zedoaria is a perennial herb that has been traditionally used as medicine. The essential oils of C. zedoaria have anti-microbial, anti-inflammatory, anti-hepatotoxic and anti-oxidant activities. In the previous studies, most researchers only focused on the phytochemical properties of C. zedoaria L. and its activities. There is lack of study on the influence of pre-treatment of the rhizome of C. zedoaria on the chemical composition and antioxidant properties. Objective: The aim of this research is to compare the chemical composition and antioxidant properties of the essential oil produced from different pre-treatment methods. Methods: The rhizomes were treated by boiling and freeze-drying before extraction of the essential oil, followed by analysis on antioxidant properties. The chemical composition of the essential oil was analysed using GC-FID and GC-MS methods. Results: Fresh rhizome of C. zedoaria produced more essential oil (0.55 %) compared to boiled (0.43 %) and freeze-dried (0.20 %) rhizomes. All samples exhibit antioxidant activity in DPPH scavenging and reducing power assays. All the pre-treatment methods had shown significant differences in antioxidant activities (p < 0.05). The essential oil from boiled pre-treatment method has higher DPPH radical scavenging activity. In reducing power assay showed that fresh rhizome has the highest antioxidant activity followed by freeze-dried and boiled rhizomes. Based on GC-MS analysis the essential oil from fresh, boiled and freeze-dried rhizomes of C. zedoaria mainly contained oxygenated monoterpenes, oxygenated sesquiterpenes, and other aliphatic compounds. Conclusion: Chemical compositions and antioxidant activities of C. zedoaria were varies with the pre-treatment methods applied.